Prevention and Handling of Gender-Based Violence from an Islamic Feminist Perspective - Dewi Masyitoh; M. N Harisuddin; Sofkhatin Khuaidah (Journal of General Education and Humanities, 2026)
This study aims to describe strategies for preventing and addressing gender-based violence from an Islamic feminist perspective by employing the Hermeneutic Theory of the Qur'an and Hadith (Feminist Interpretation) and Gender Equity Theory as analytical frameworks. Gender-based violence remains a significant social and humanitarian issue that requires comprehensive approaches grounded in religious, social, and psychological dimensions. This research adopts a descriptive qualitative approach to explore prevention efforts and victim assistance practices within an Islamic feminist framework. Primary data were collected through in-depth interviews with five informants: two religious leaders (one male and one female), two counselors, and one psychologist affiliated with LKP3A Fatayat NU Bondowoso. Data were analyzed through processes of data reduction, categorization, interpretation, and verification to identify patterns of prevention and intervention strategies. The findings reveal that prevention efforts are undertaken through the reinterpretation of patriarchal and misogynistic understandings of Qur'anic verses and Hadith traditions, replacing them with egalitarian interpretations that emphasize justice, equality, and human dignity. These preventive strategies are implemented through community outreach programs, educational activities, awareness campaigns, and religious guidance to promote gender-sensitive perspectives. Furthermore, victim assistance integrates psychological recovery with spiritual empowerment, grounded in the concepts of human dignity (karamah insaniyah) and human nature (fitrah), within the framework of Islamic counseling. Assistance services also encompass legal advocacy and protection mechanisms to ensure victims receive comprehensive support. This study highlights the importance of Islamic feminist approaches in developing inclusive, transformative, and justice-oriented strategies for preventing and responding to gender-based violence.